2016
DOI: 10.4013/htu.2016.203.04
|View full text |Cite
|
Sign up to set email alerts
|

Imigração alemã ao Brasil (século XIX) e Prússia: fronteiras permeáveis e diálogos entre história global e micro-história

Abstract: Resumo: O artigo seguinte reflete sobre as potenciais vantagens da incorporação e integração das perspectivas e abordagens da história global e micro-história para a pesquisa em imigração alemã no Brasil, particularmente durante o século XIX. Percebe-se que uma parte importante dos estudos em imigração alemã no Brasil não têm levado em devida consideração a dimensão europeia e global do fenômeno, aspectos centrais para se entender o processo de renegociação sociocultural ocorrido em território brasileiro. Atra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
1
0
1
Order By: Relevance
“…In the late nineteenth century, several groups, largely formed by Prussians (from Hunsrück, Eifel, Rhineland in general, Pomerania, Westphalia and Silesia) and their descendants landed in Brazil and formed colonies in the Northeast, Southeast and South regions of the country [2]. According to research carried out based on historical sources to classify the ancestry of Brazilian surnames, it was shown that, in a universe https://doi.org/10.1590/1678-9865202134e200048 of 46,801,772 Brazilian names reviewed, 1,525,890 or 3.3% of individuals had the only or last name indicating a German ancestry [3].…”
Section: Introductionmentioning
confidence: 99%
“…In the late nineteenth century, several groups, largely formed by Prussians (from Hunsrück, Eifel, Rhineland in general, Pomerania, Westphalia and Silesia) and their descendants landed in Brazil and formed colonies in the Northeast, Southeast and South regions of the country [2]. According to research carried out based on historical sources to classify the ancestry of Brazilian surnames, it was shown that, in a universe https://doi.org/10.1590/1678-9865202134e200048 of 46,801,772 Brazilian names reviewed, 1,525,890 or 3.3% of individuals had the only or last name indicating a German ancestry [3].…”
Section: Introductionmentioning
confidence: 99%
“…Para tanto, promove-se uma aproximação dos procedimentos utilizados pela micro-história com as práticas adotadas por Eliane Brum para a investigação, apuração e escuta das personagens. Levi (2015) salienta que os documentos sintetizam realidades "parciais" e "mentirosas". Os arquivospara o historiador italiano, emergem em situações de decisão e ação -relegando para segundo plano noções mais subjetivas, como as hesitações, os sentimentos, as emoções e as esperanças.…”
Section: Introductionunclassified